Application Quality, Product Innovation, and Popularity in Influencing Shopee Consumer Satisfaction and Repurchase Intentions in Indonesia - Alfath Ibrahim; Anas Hidayat (Jurnal Mantik, 2022)
The use of e-commerce as a medium for online goods and service transactions has increased every year, including shopping. In its application, the quality of the application, product innovation, and product popularity is of concern to various parties. This study aims to analyze the correlation between application quality, product innovation, and popularity influencing the satisfaction and repurchase intentions of Shopee consumers in Indonesia. Quantitative research with a statistical approach was used in this study. Primary data came from Indonesia, where 314 people filled out questionnaires sent through google forms. The data was taken using non-probability sampling, and the data analysts used structural equations models with AMOS. The results showed that the satisfaction and repurchase intentions of shopping consumers in Indonesia were influenced by product quality (p = 0.000) and popular products (p = 0.000) but not influenced by product innovation (p = 0.071). Consumer satisfaction directly affects repurchase intentions of Shopee consumers in Indonesia. Hence, shopping service providers need to improve the quality and popularity of their products and support them with new ideas to make customers happier and more likely to buy again.